Interactive Multimedia Development in Futsal Basic Techniques - Iqbal, Muhammad Iqbal; Asmawi, Moch Asmawi; Tangkudung, James Tangkudung; Dlis, Firmansyah Dlis; Saputra, Surya Adi (Journal of Education, Health and Sport, 2019)
The purpose of this research is to develop some basic techniques and makeup products in the form of variations of exercises and training videos so that they can Easily be learned by the general public. In this study using the Research and Development Adopted method from borg and gall. The needs analysis was Carried out with 35 subjects as students who had passed the futsal course. Small group test with a sample of 12 people with good results then proceed to the large group stage with a sample of 40 people with good results and Proceeds to a PACT test with a total of 2 people and Obtained good results and can be used in actual practice. Based on the hypothesis testing and calculation criteria Obtained Sig. = 0036 <, it can be concluded that H0 is rejected. Thus, it was concluded that there were significant differences in the results of the posttest and pretest between before and after treatment being given interactive multimedia, where the results of the posttest effectiveness test were higher than Reviews those of the pretest. Based on this information it can be said that the interactive multimedia-based interactive skills playing futsal training the model is effective and can improve skills playing futsal. Based on the results of the study it can be concluded that the futsal-based interactive multimedia models developed playing skills training has significant effectiveness.